Adverse childhood experiences, subsequent negative life events, and their impact on health in occupational rehabilitation patients: a mixed-methods study - Eftedal, Monica; Johansen, Thomas; Del Risco Kollerud, Ruby (Frontiers in Rehabilitation Sciences, 2024)
IntroductionAdverse childhood experiences (ACEs) are prevalent globally and can negatively impact an individual's lifespan by not only increasing the likelihood of encountering other negative life events (NLEs), but also escalating the risk of illness, absenteeism due to sickness, unemployment, and reliance on disability benefits in adulthood. Therefore, the objective of this study was to explore the prevalence of ACEs and NLEs, as well as their health impacts among patients undergoing occupational rehabilitation.Materials and methodsA total of 80 participants diagnosed with musculoskeletal disorders and/or common mental disorders who participated in two occupational rehabilitation programs in Norway were included. Data were collected by questionnaire and in-depth interviews (39 participants) at the start of the intervention. Comparative quantitative and qualitative analysis was conducted between individuals with a history of ACEs and those without these experiences. Thematic analysis was used to identify the impact of ACEs and NLEs on the health of the informants.ResultsHalf of the participants reported ACEs. Of these, 18% reported one ACE, 22% reported 2–3 ACEs and 9% reported 4 or more ACEs. Also, 25% were categorized as revictimized. The two groups with ACEs had more NLEs in adulthood compared to those without ACEs (p < 0.001), revictimized the most (mean numbers between groups 3.1, 4.5 and 5.9). Furthermore, a history of ACEs was associated with a higher number of reported mental health issues compared to those who had not experienced ACEs (p < 0.01). However, there were no significant differences between the two ACE groups. NLEs had a substantial impact on the participants’ current health status, whether they occurred in childhood or adulthood. In adult life, a high workload (psychologically or physically), interpersonal challenges, and financial struggles had an especially negative impact. Additionally, accidents and complications related to surgeries were also significant NLEs causing health problems. For most, there were complex interactions between NLEs and health.ConclusionsThe prevalence of ACEs and NLEs is high among occupational rehabilitation patients. ACEs are associated with subsequent victimization, interpersonal challenges, financial struggles, and increased mental health issues in adulthood. These findings highlight the need for systematic screening and a holistic, individualized approach in occupational rehabilitation programs to potentially mitigate the adverse effects of NLEs on health and work participation.